Handbook of affect and social cognition - Forgas, Joseph P. (Erlbaum, 2001)
Introduction: affect and social cognition / Joseph P. Forgas -- The interaction of affect and cognition: a neurobiological perspective / Ralph Adolphs and Antonio R. Damasio -- Affect and attitudes: a social neuroscience approach / Tiffany A. Ito and John T. Cacioppo -- Affect and cognitive appraisal processes / Craig A. Smith and Leslie D. Kirby -- Mood and social memory / Gordon H. Bower and Joseph P. Forgas -- Affect as information / Gerald L. Clore, Karen Gasper, and Erika Garvin -- Affective influences on the self-concept: qualifying the mood-congruency principle / Constantine Sedikides and Jeffrey D. Green -- Affective influences on social information processing / Klaus Fiedler -- Promotion and prevention experiences: relating emotions to nonemotional motivational states / E. Tory Higgins -- The role of affect in attitude change / Richard E. Petty, David DeSteno, and Derek D. Rucker -- The role of affect in cognitive-dissonance processes / Eddie Harmon-Jones -- Mood as a resource in processing self-relevant information / Yaacov Trope, Melissa Ferguson, and Raj Raghunathan -- The role of motivated social cognition in the regulation of affective states / Maureen Wang Erber and Ralph Erber -- Affect, cognition, and interpersonal behavior: the mediating role of processing strategies / Joseph P. Forgas -- Affective influences on stereotyping and intergroup relations / Galen V. Bodenhausen, Thomas Mussweiler, Shira Gabriel, and Kristen N. Moreno -- Affect and health-relevant cognition / Peter Salovey, Jerusha B. Detweiler, Wayne T. Steward, and Brian T. Bedell -- Personality as a moderator of affective influences on cognition / Cheryl L. Rusting -- Affect, stress, and personality / Jerry Suls -- Emotion, intelligence, and emotional intelligence / John D. Mayer
Literaturangaben
Keywords: Soziale Wahrnehmung; Affekt